Performance Characteristics Of Brushless Direct Current (BLDC) Motor 350W 36V As The Driving Motor Of An Electric Bicycle - Setyawan et al., Choirul Adi (Universitas Merdeka Malang, 2025)
This research aims to determine the performance characteristics of a BLDC motor 350W 36V as the driving motor of an electric bicycle at varying speeds of 10 km/hour, 20 km/hour and 30 km/hour. The distance traveled in this test is 1 km on flat road conditions with a load of 1 (one) rider of 75 kg. The test was carried out by recording the load value in the form of BLDC motor power and the duration of use of the battery when the electric bicycle was ridden. The test results show that at a speed of 10 km/hour an average motor load was recorded at 61.65 watts, at a speed of 20 km/hour an average load was recorded at 154.09 watts and at a speed of 30 km/hour an average load was recorded at 315.65 watts. The duration of use of the battery is that at a constant speed of 10 km/hour the battery can last for 4,2 hours, at a constant speed of 20 km/hour the battery can last for 1.68 hours and at a constant speed of 30 km/hour the battery can last for 0.82 hour